Analisis Strategi Pemasaran Rotte Bakery Di Kota Duri Dalam Menghadapi Persaingan Usaha Menurut Perspektif Ekonomi Islam - Hermawan, Sandy; Fitri, (Journal of Islamic Banking, Economics and Finance, 2024)
The aim of this research is to see how Rotte Bakery's marketing strategy in Duri city is in facing business competition and what the Islamic economic perspective is about Rotte Bakery's marketing strategy in Duri city. The methods for collecting data are observation, interviews and documentation. Meanwhile, the data analysis technique used is qualitative with a descriptive approach. Based on the research results, it shows that the marketing strategy implemented by Rotte Bakery in the city of Duri is by implementing market segmentation, targeting, positioning and the 4P marketing mix which consists of product, price, place and promotion strategies. Review of the Islamic economic perspective on the marketing strategy of Rotte Bakery in the city of Duri in accordance with Islamic marketing strategy, because Rotte Bakery is a sharia (religious) based bakery business that combines their business with marketing practices and the characteristics of the Prophet Muhammad SAW, namely Shiddiq (honest), Amanah (able trustworthy), Fathanah (intelligent), and Tabligh (communicative) so that the business carried out will receive approval and blessings from Allah SWT.